-9+6v=v-5+6v

Simple and best practice solution for -9+6v=v-5+6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9+6v=v-5+6v equation:


Simplifying
-9 + 6v = v + -5 + 6v

Reorder the terms:
-9 + 6v = -5 + v + 6v

Combine like terms: v + 6v = 7v
-9 + 6v = -5 + 7v

Solving
-9 + 6v = -5 + 7v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-7v' to each side of the equation.
-9 + 6v + -7v = -5 + 7v + -7v

Combine like terms: 6v + -7v = -1v
-9 + -1v = -5 + 7v + -7v

Combine like terms: 7v + -7v = 0
-9 + -1v = -5 + 0
-9 + -1v = -5

Add '9' to each side of the equation.
-9 + 9 + -1v = -5 + 9

Combine like terms: -9 + 9 = 0
0 + -1v = -5 + 9
-1v = -5 + 9

Combine like terms: -5 + 9 = 4
-1v = 4

Divide each side by '-1'.
v = -4

Simplifying
v = -4

See similar equations:

| 2X/4+3X/9 | | 2X/4+3X/9+4X/16+5X/25 | | 5a-6b-2a+3b= | | -q-13=2q+5 | | -1+3p=-1p-5p | | 8=4z-3z^2+15 | | x-12=48 | | -5x-2=4-4x | | 5p+6p-y-2p+4y= | | 5*n-7=38 | | 6m-3=-10-6(2-m) | | t+5t+4t-7=17 | | 4-3a=8-4a | | 1x+2=32x-160+80x-70 | | 4x+5/2x+3 | | 5x^2+15x+90=0 | | 7*y-3*y-14=14 | | -x-3x+5=4x+5 | | 2x+4/2x+3 | | 18x^2-48x-50=0 | | 10+-1=25 | | 8+3n=4n+2 | | X^3-18=9x-2x^2 | | -5=-14+7 | | a/4-7=10 | | 3x-3(-4x+12)=9 | | -9a^9+(-7a^9-5)= | | x^2+71=-18x-9 | | 2/2-x=x+1/1-x | | 13(-2)-4y=-66 | | 3x+2.1=0 | | 8x+4-7x=8-22 |

Equations solver categories